2004
DOI: 10.5993/ajhb.28.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Social Support at Work on Depression and Organizational Productivity

Abstract: Objective: To examine how social support at work affects depression and organizational productivity in a work-stress framework. Methods: A self-administered survey for 240 workers in a public hospital in the southeastern United States. Results: Social support at work was directly related to high job control, low depression, and high job performance. Social support did not buffer the negative effects of work factors on depression and organizational productivity. Conclusions: Social support at work had a direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 37 publications
4
85
1
3
Order By: Relevance
“…Regehr et al suggested that low social support is an important determinant of depressive symptoms and PTSD among firefighters. 26,27 Consistent with previous findings, 28,29 psychosocial factors such as supervisor and family support were also important factors related to depressive symptoms among NOFD personnel. Those who reported that they were living with their families had a lower risk of depressive symptoms.…”
supporting
confidence: 78%
“…Regehr et al suggested that low social support is an important determinant of depressive symptoms and PTSD among firefighters. 26,27 Consistent with previous findings, 28,29 psychosocial factors such as supervisor and family support were also important factors related to depressive symptoms among NOFD personnel. Those who reported that they were living with their families had a lower risk of depressive symptoms.…”
supporting
confidence: 78%
“…A considerable number of studies in social support and well-being have verified that social support can relieve an entity of pressure, maintain mental health and increase well-being at work (Holt-Lunstad, Smith, & Layton, 2010;Toker, 2011;Cohen & Syme, 1985;Cohen, 1998;Karademas, 2006;Park, Wilson, & Lee, 2004). Kruger (1997) found that social support is to support and evaluate the interventions of teachers to solve students' behavior problems.…”
Section: Social Supportmentioning
confidence: 99%
“…Investigators have assessed work stress among medical technicians [8], radiation therapists [9], social workers [20], occupational therapists [11], physicians [12,13], and collections of health care staff across disciplines [14,15]. Nevertheless, work stress and burnout remain significant concerns in nursing, affecting both individuals and organizations [16].…”
Section: Discussionmentioning
confidence: 99%